PROSEDUR MENULIS KARANGAN DESKRIPSI PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS IV SDN ANAM - Stanislaus Hermaditoyo; Emiliana Anita Triniati (JIPD (Jurnal Inovasi Pendidikan Dasar), 2023)
Problems discussed in research about the procedure of writing essay description of fourth grade students at SDN Anam showed that the understanding of fourth grade students of SDN Anam was still low. This research aims to describe the procedure of writing essay description of students on the subjects of Indonesian class IV in SDN Anam District Ruteng. The subjects of this study are students of SDN Anam, amounting to 16 people. In this research the data retrieval technique by using the test instrument. This test is used to know the students understanding. The type of research used is qualitative-descriptive research, the researcher collect data related to the description writing procedure which then the data will be analyzed using the steps proposed by Miles and Hubermen namely, data reduction, data presentation, and conclusion. The results of this study indicate that there are total errors made by students divided into two articles that do not choose the topic or 12.5, one student observation or 6.25%, sixteen students collect data in the form of examples, drawings, graphs , Or statistics as illustrations or 100%, two sets of students establish appropriate and appropriate development patterns or 12.5%, two articles of students who do not compose a paragraph framework of basic ideas and explanatory ideas or 12.5%, two essays do not develop The framework becomes a whole paragraph using logical and cohesive sentences or 12.5%, three essays do not edit text / paragraph description or 18.75%, two uppercase or unsuitable capital letters or 12.5%, two Not using punctuation correctly or 12.5%. This indicates the learning of Indonesian about Procedure Writing essay Description not maximal yet. Keywords: Procedures, Writing, Essay Description